Les démarches et problèmes à résoudre dans les études comparatives — la prédication nominale en français et en polonais - Vetulani, Grażyna (Neophilologica, 2018)
Observations collected in this paper result from our research on predicate nominatives in French and Polish. We focus on: 1) definition of the concept of predication in French versus Polish language linguistic tradition, 2) methodological issues concerning data acquisition and description procedures; traditional versus computer-assisted methods, 3) evaluation of reference corpora used for acquisition of predicative nouns in both concerned languages, 4) format of lexicographical descriptions of predicative expressions.